Continuous Melt‐Drawing of Highly Aligned Flexible and Stretchable Semiconducting Microfibers for Organic Electronics. (24th November 2017) - Zhao, Yan; Gumyusenge, Aristide; He, Jiazhi; Qu, Ge; McNutt, William W.; Long, Yuan; Zhang, Hongyi; Huang, Libai; Diao, Ying; Mei, Jianguo
Abstract: A scalable and green approach to manufacture semiconducting microfibers from polymer melts has been demonstrated. The polymer chains are highly aligned along the microfiber's long axis direction and exhibit highly anisotropic optical properties. In addition, the polymer microfibers show good flexibility and stretchability with a yield point around 10% under a reversible stress and can be stretched up to 180% without breaking. These features are desired for future flexible, stretchable, and conformable electronics. The origin of this stretchability is studied with diketopyrrolopyrrole derivatives using different conjugation break spacers and side chains. In addition, stretchable conducting microfibers can be obtained by doping with FeCl3, which are further evaluated as organic conductors and source/drain electrodes in organic field‐effect transistors. Abstract : Highly aligned flexible and stretchable microfibers are manufactured by continuously drawing from semiconducting polymer melts, which exhibit highly anisotropic optical and electronic properties. The polymer microfibers have a yield point around 10% under reversible stress and can be stretched up to 180% without breaking. After doping by FeCl3, the polymer microfibers can also be used as stretchable conducting fibers and electrodes, and show great potential in organic electronics.